Kue Lumpur Substitusi Tepung Kulit Buah Naga Merah sebagai Makanan Selingan Mengandung Antioksidan - Marella Adhania Dewanto; Heri Warsito; Alinea Dwi Elisanti (PT FORMOSA CENDEKIA GLOBAL, 2022)
Free radicals and consumption of unbalanced nutritional needs become the main cause of degenerative diseases. This study aims to examine the manufacture of mud cakes substituted with red dragon fruit peel flour (Hylocereus polyrhizus) as a source of antioxidants. This study using a completely randomized design with 5 treatment formulations of red dragon fruit peel flour: wheat flour is 5%:95%, 10%:90%, 15%:85%, 20%:80%, 25%:75% with 5 repetitions. The antioxidant activity was between 9,8-19,4%. The best treatment was P1 (5% red dragon fruit peel flour: 95% wheat flour) with 9,8% antioxidant activity. The serving size of mud cake is two pieces (weight are 150g), the nutritional value is 301.5kcal of energy, 9.6g of protein, 16.5g of fat, 28.5g of carbohydrates.